Serum microRNAs as Diagnostic Markers in Polycystic Ovary Syndrome: A Narrative Review - K Lavanya; N Palaniappan; VM Vinodhini; Santhi Silambanan (Journal of Clinical and Diagnostic Research)
Polycystic Ovarian Syndrome (PCOS) is thought to be common worldwide among middle-aged women. Increased androgen production, recurrent anovulatory cycles and ovaries with multiple cysts are symptoms of this multiorgan endocrine condition. MicroRNAs (miRs) and several candidate genes, including CYP11A, CYP21 and CYP17, have been linked to PCOS. Single-stranded non coding RNAs known as microRNAs have been shown to alter several cell cycle processes, including metabolism, apoptosis, differentiation and proliferation. By targeting hormone receptors and their release, microRNAs influence the production of steroid hormones and play a significant role in the formation and regulation of follicular growth in the ovaries. Physiological development, including physical growth and embryonic development of the ovaries, alter the levels of microRNA expression. It has been discovered that the altered pattern of microRNAs under pathological circumstances is specific to certain disorders. Therefore, a variety of medications that are either agonists or antagonists of microRNAs may be useful in initiating tailored treatments. The profiles of microRNAs differ depending on the tissue from which they originate. Due to ribozyme activity, microRNAs are persistent and resistant to hydrolysis. Since serum microRNAs are present in various bodily fluids, they are novel markers for diseases like PCOS. The microRNA profile constantly changes depending on the pathogenic stage of the disease. There are correlations between the levels of established biomarkers and the up- and down-regulation of certain microRNAs. Furthermore, it has been found that microRNAs are more specific and sensitive than conventional biomarkers. This article was created to address the altered microRNA profiles in systemic circulation and in different ovarian tissues.